2022
DOI: 10.1111/risa.14032
|View full text |Cite
|
Sign up to set email alerts
|

Media exposure, threat processing, and mitigation behaviors in Gulf Coast residents facing the co‐occurring threats of COVID‐19 and hurricanes

Abstract: The 2020 hurricane season threatened millions of Americans concurrently grappling with COVID‐19. Processes guiding individual‐level mitigation for these conceptually distinct threats, one novel and chronic (COVID‐19), the other familiar and episodic (hurricanes), are unknown. Theories of health protective behaviors suggest that inputs from external stimuli (e.g., traditional and social media) lead to threat processing, including perceived efficacy (self‐ and response) and perceived threat (susceptibility and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…At W2, COVID-19-related health protective behaviors were assessed on a scale of 1 ( never ) to 5 ( all the time ) and included: (a) wearing a facemask in public and (b) social distancing, a composite of four items (see ). Social distancing items were averaged (see Garfin et al, 2021, 2023). At W3, vaccination intentions and behaviors were assessed with the following items: “Have you gotten the COVID-19 vaccine?” with response options 1 ( yes, voluntarily ), 2 ( yes, but only because I was required to by my employer/school ), 3 ( no, but I plan to ), 4 ( no, and I do not plan to ), and 5 ( no, I am medically unable ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At W2, COVID-19-related health protective behaviors were assessed on a scale of 1 ( never ) to 5 ( all the time ) and included: (a) wearing a facemask in public and (b) social distancing, a composite of four items (see ). Social distancing items were averaged (see Garfin et al, 2021, 2023). At W3, vaccination intentions and behaviors were assessed with the following items: “Have you gotten the COVID-19 vaccine?” with response options 1 ( yes, voluntarily ), 2 ( yes, but only because I was required to by my employer/school ), 3 ( no, but I plan to ), 4 ( no, and I do not plan to ), and 5 ( no, I am medically unable ).…”
Section: Methodsmentioning
confidence: 99%
“…At W2, COVID-19-related health protective behaviors were assessed on a scale of 1 (never) to 5 (all the time) and included: (a) wearing a facemask in public and (b) social distancing, a composite of four items (see SF1 in the online supplemental materials). Social distancing items were averaged (see Garfin et al, 2021Garfin et al, , 2023. At W3, vaccination intentions and behaviors were assessed with the following items: "Have you gotten the COVID-19 vaccine?"…”
Section: Behaviorsmentioning
confidence: 99%
“…In general, perceptions of efficacy are strongly associated with initiating and maintaining adaptive behaviors (Strecher et al 1986). Prior analyses demonstrated that efficacy was associated with preparation for hurricanes (Garfin et al 2023), which are projected to intensify because of climate change (Bloemendaal et al 2022;Emanuel 2020). In the context of climate change behaviors specifically, perceptions of collective efficacy related to the ability to change the system (Roser-Renouf et al 2014) and individual efficacy (the extent to which one can personally mitigate climate change) (Hornsey et al 2021) are important correlates of climate change-related sustainability behaviors.…”
Section: Perceived Efficacy Of Climate Change-related Sustainability ...mentioning
confidence: 99%